Da riqueza à lama: análise da dinâmica socioeconômica do município de Mariana (MG) após o rompimento da Barragem do Fundão - Santos, Vinicius Fortes da Silva (2018)
Mining is an important activity for Minas Gerais, being directly related to the process of historical constitution of the economic dynamics and the social development of the state. Mariana is one of the municipalities in Minas Gerais where mineral extraction is representative of the capacity to generate employment and income. Despite the economic performance, due to the rupture of the Fundão Dam on November 5, 2015, the municipality carried out the biggest environmental accident in Brazil. Thus, the present study proposes to analyze the socioeconomic consequences of the disaster on the living conditions of the population, as well as on the conditions of reproduction of the economic enterprises of the municipality. For that, a bibliographical, documentary and field research was carried out. They were used for instrumental analysis in descriptive statistics and the operationalization of indexes, based especially on the Alkire-Foster method and fuzzy inference systems. The observation of secondary data allowed us to detect that the number of jobs, the average salary and the tax revenue in Mariana declined in the period after the environmental disaster. The proportion of poor individuals and the level of deprivation also increased in the interstice from 2010 to 2018. The fuzzy perception of impact index reveals that local agents consider that the incident in Bento Rodrigues has generated consequent on the social well-being and its capacities socioeconomic reproduction. Therefore, it is inferred that important public actions should be focused to promote the resumption of economic growth, as well as the quality of life of the population of Mariana. Strategies for sustainable development deserve attention from the public authorities, particularly since they can overcome the socio-environmental vulnerabilities that have been unleashed since 2015.